Antithrombotic therapy and clinical characteristics of patients hospitalized for nonvalvular atrial fibrillation in Galician internal medicine clinics - Cerqueiro-González, José Manuel; Fernández-Bouza, Elena; López-Reboiro, Manuel Lorenzo; Pesqueira-Fontán, Paula; Vázquez-Rodríguez, Patricia; Novo-Veleiro, Ignacio; Casariego-Vales, Emilio (Journal of Cardiovascular Medicine and Cardiology, 2019)
This was a multicenter, prospective, observational study that assessed the characteristics of patients with Nonvalvular Atrial Fibrillation (NVAF) admitted to internal medicine units in Galicia, Spain, as well as the antithrombotic treatment prescribed prior to hospital admission. Demographic characteristics, cardiovascular risk factors, polypharmacy, comorbidity, functional status and reasons for hospitalization were recorded for patients with NVAF admitted between January 2016 and January 2017. The antithrombotic treatment received by patients prior to hospital admission and the reasons for using this treatment were also analyzed. A total of 1419 patients were included (mean age 82.1 years; 50% male). The mean (standard deviation) number of chronic diseases per patient was 4.11(2.14) and the number of drugs being taken was 9.66(4.60). The mean CHA2DS2-VASc score was 3.09(1.26). NVAF-related hospitalizations accounted for 37.5% of all hospital admissions, with heart failure the most common reason for hospitalization (31.4%). Most patients (75.1%) with NVAF were on anticoagulants at the time of admission and direct oral anticoagulants accounted for 13.9% of anticoagulants. Functional status was the only factor associated with the use of anticoagulation therapy. In conclusion, patients with NVAF admitted to Galician internal medicine units are a diverse population. More than one third are hospitalized for causes related to NVAF, while one in four is not receiving the appropriate antithrombotic therapy. The data suggest that, when primary care physicians or a specialist prescribe antithrombotic therapy, the patient’s functional status is more relevant than established risk factors to their decision-making.